„Paraklet (…) przekona świat o grzechu, o sprawiedliwości i o sądzie”. Jana Pawła II pneumatologiczna hermeneutyka J 16, 7–8 - Dudek-Kowalska, Agnieszka (Warszawskie Studia Teologiczne, 2022)
The multidimensional meaning of the triad: the sin, the justice and the judgement in the teaching of Pope John Paul II leads to the conclusion, that the Truth revealed in this way by the Holy Spirit is a vivid, dynamic and even personal reality and first of all it is targeted to the man and his salvation. The truth in the theological meaning shown by John Paul II has its source in the loving, saving will of God. In this meaning the truth is always on the side of man’s good. It is never against him. The Truth is the answer to the untruth, to the sin. It restores the justice. It sentences everything that doesn’t refer to the Truth. The relationship between the presence of the Holy Spirit in the history of the world and the existence of the truth leads to the conclusion that the truth as such, the truth in the theological and philosophical meaning doesn’t depend on the man’s will. In the innermost layer its origin is divine. In the consequence the man does not decide about the existence of the truth and in the further consequence about the existence of the order of nature and things. However the man is liable for non-cognition of the truth and the lack of adoption of the truth. To adopt the truth in life one needs humility, needs to break the barriers of one’s egoism and to recognize one’s limitation. The truth is the base of human being and the human destination. The crisis existing around the truth is the crisis of the man in the deepest meaning. The lack of the relationship with the truth reduces the man to the materialistic level and the living contingency. The openness to the truth is the openness to God, who restored the justice in the creature by His Son Jesus Christ and made the judgement of the untruth.